Housing Finance and Real-Estate Booms : A Cross-Country Perspective - Cerutti, Eugenio (Staff Discussion Notes; Staff Discussion Notes, 2015)
The recent global crisis highlighted the risks stemming from real estate booms. This has generated a growing literature trying to better understand the sources and the risks associated with housing and credit booms. This paper complements and supplements the previous work by (i) exploiting more disaggregated data on credit allowing us to dissociate between firm-credit and household (and in some cases mortgage) credit, and (ii) by taking into account the characteristics of the mortgage market, including institutional as well as other factors that vary across countries. This detailed cross-country analysis offers new valuable insights.